Performance of Ruzi Grass Combined with Woven Limited Life Geotextiles (LLGS) for Soil Erosion Control - S. Artidteang; D.T. Bergado; S. Chaiyaput; T. Tanchaisawat; L.G. Lam (International Association of Lowland Technology, 2016)
Natural fibers can be made into woven geotextile and combined with growing vegetation for slope protection. Thailand has highly abundant natural fibers and rural communities have been converting them into handicrafts. The water hyacinth yarns were fabricated to woven geotextile called limited life geotextiles (LLGs) to help stabilize the slope and improved the growth of vegetation for erosion control in geotechnical application. The study was aimed to assess the effectiveness of the LLGs new material for geotextile made from water hyacinth combined with Ruzi grass to control soil erosion in a representative slope. The erosion control test was performed by using the artificial rainfall. The flow rates of water runoff and amount of soil loss were investigated. Consequently, the limited life geotextiles made from water hyacinth LLGs combined with Ruzi grass can reduce the flow rate of runoff and amount of soil loss.